Kepemimpinan Kiai dalam Mengembangkan Pondok Pesantren - Umam, Wafiqul (CV. Creative Tugu Pena, 2020)
Pondok Pesantren is one of the oldest educational institutions in Indonesia. The significance of the kiai's role in the boarding school is directly proportional to his leadership in managing and directing the entire community in his cottage, especially the students and their influence in society. While the model in leading his Islamic boarding school, each kiai has his own method for advancing his pesantren. This happened because of the kiai's focus on developing his boarding school and the environmental conditions of the surrounding community. This article was describe how the leadership role of kiai in Islamic boarding schools in developing the institutions. This research was descriptive research methods with a qualitative research approach. The main finding in the researcher was the figure of a kiai with his charismatic character that able to have a positive effect in the development of the Islamic boarding schools. Hence bringing the boarding school into the main choice for the community and parents in particular. Keywords: The Leadership of Kiai, The development of Pesantren